World trends in the application of accelerators for the production of basic isotopes for nuclear medicine - Guk, I.S. (Вопросы атомной науки и техники, 2022)
The basic isotopes of nuclear medicine presently are ⁹⁹Mо and ¹⁸F. For the production of these isotopes, there was a need to create accelerators to satisfy the needs for isotopes for large countries. For these purposes, electron accelerators are developed using warm and superconducting accelerating structures. It is also assumed to use neutron generators and cyclotrons. Основними ізотопами ядерної медицини в даний час є ⁹⁹Mо і ¹⁸F. Для виробництва цих ізотопів виникла необхідність створення прискорювачів, що дозволяють задовольнити потреби в ізотопах для великих країн. Для цих цілей розроблені електронні прискорювачі, що використовують теплі і надпровідні прискорюючі структури. Також передбачається використовувати нейтронні генератори і циклотрони. Основными изотопами ядерной медицины в настоящее время являются ⁹⁹Mо и ¹⁸F. Для производства этих изотопов возникла необходимость создания ускорителей, позволяющих удовлетворить потребности в изотопах для больших стран. Для этих целей разработаны электронные ускорители, использующие теплые и сверхпроводящие ускоряющие структуры. Также предполагается использовать нейтронные генераторы и циклотроны.